Life cycle assessment as a diagnostic and planning tool for waste management-a case study in a Brazilian municipality - Paes, Michel Xocaira [UNESP]; Mancini, Sandro Donnini [UNESP]; De Medeiros, Gerson Araújo [UNESP]; Bortoleto, Ana Paula; Kulay, Luiz Alexandre (Journal of Solid Waste Technology and Management, 2018)
This paper discusses an evaluation of the environmental impacts of a Municipal Solid Waste Management System using Life Cycle Assessment (LCA), with a view to the proposal of improvement actions, the support of decision-making processes, and the establishment of public policies. This study was developed based on an analysis of the solid waste management system of the city of Sorocaba, Brazil (600,000 inhabitants). The LCA was performed using the CML baseline 2000 method of impact assessment. The system consists primarily of the ordinary collection and disposal in a landfill of 488 tons/day of solid wastes containing more than 40% of organic matter and a selective collection which diverts only 17 tons/day of the wastes from landfilling. It was found that emissions of methane in the landfill are responsible for 62% of all the impacts, followed by the transport of ordinary wastes (34.2%). Actions such as increased recycling and the development of composting, anaerobic digestion and incineration of waste would significantly reduce the amount of landfill waste, and hence, the impacts of landfilling. The burning of methane and the use of biofuels by the fleet should be immediately implemented to reduce the impacts provided by this waste management system.
Keywords: Environmental impacts; Life cycle assessment (LCA); Municipal solid waste; Public policy; Waste management